Prediction of cassava starch edible film properties by chemometric analysis of infrared spectra - Vicentini, N. M.; Dupuy, N.; Leitzelman, M.; Cereda, M. P.; Sobral, PJA (Taylor & Francis Inc, 2005)
Cassava starch has been shown to make transparent and colorless flexible films without any previous chemical treatment. The functional properties of edible films are influenced by starch properties, including chain conformation, molecular bonding, crystallinity, and water content. Fourier-transform infrared (FTIR) spectroscopy in combination with attenuated total reflectance (ATR) has been applied for the elucidation of the structure and conformation of carbohydrates. This technique associated with chemometric data processing could indicate the relationship between the structural parameters and the functional properties of cassava starch-based edible films. Successful prediction of the functional properties values of the starch-based films was achieved by partial least squares regression data. The results showed that presence of the hydroxyl group on carbon 6 of the cyclic part of glucose is directly correlated with the functional properties of cassava starch films.
Keywords: cassava; chemometric analysis; edible film; Fourier-transform infrared spectroscopy; starch